The Effects of Rectilinear Acceleration and Deceleration on Shock Formation near a Stationary Boundary - Morrow, Sean Robert (University of the Witwatersrand, Johannesburg, 2024)
Inspired by the world land speed record vehicles the Thrust and Bloodhound supersonic cars (SSC), the focus of this dissertation is to investigate how rapid acceleration affects the formation of shock waves coming off an object travelling in ground effect. Due to the proximity of the ground, these shock waves are not able to freely propagate under the object and must interact with, and reflect off, the ground. Steady state and transient models of aerofoils, accelerating from Mach 0.05 to Mach 2.00 at a test run acceleration of 3 g and an extreme acceleration of 176 g are developed and compared to reveal that the transient shock wave development trails that of the constant velocity aerofoil. The main reason for this difference is that the transient flow is unable to fully develop and reach a state of equilibrium. The extreme acceleration allowed even less time for the flow to develop, and the difference in the shock location continuously increased throughout the acceleration. The same difference in shock location was evident when these models were decelerated back down to Mach 0.05. However, the extreme deceleration and increasing difference in shock location drastically changed the transonic and subsonic flow field, especially as flow features and shock waves from the higher velocity flow overtook the model. In each acceleration and deceleration case, the transient flow history effects subsided and the aerodynamic performance from the transient analysis converged with the aerodynamic performance from the steady state analysis. Under acceleration the transient performance converged at a higher steady state Mach number, while under deceleration the transient performance converged at a lower steady state Mach number. As the magnitude of the acceleration and deceleration increased the Mach number at which the results converged shifted to higher and lower Mach numbers respectively. Models with different orientations and ground clearances were also compared against each other and a case at free flight to determine the impact ground effect has on the formations and locations of the shock waves. Increasing ground effect was shown to promote the formation of shock waves under the inverted aerofoil and in general delay the propagation of the bow shock between the model and the ground. Once the bow shock propagations passed underneath the models, the resulting flow field converged with free flight conditions and ground effect no longer had an impact on the supersonic aerodynamic performance of these models. Under some conditions, the combination of ground effect and the transient effects of acceleration or deceleration can cause dangerous lift and pitch conditions.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: SDG-9: Industry, innovation and infrastructure